Organizational job related stress and its consequences on employees / Wan Hanisah Wan Ismail - Wan Ismail, Wan Hanisah (Universiti Teknologi MARA Cawangan Pahang, 2000)
(Tunggu keyword) Workplace condition is an important element to ensure job satisfaction and maintain employee work health and productivity. But in recent years reports of job distress have been seen to be on the rise. Stress related disorders and consequenses has been reported to affect job performance, increase turnover rate and induce illnesses among employees in working organizations. This paper describes some of the common work stressors and their consequences in the working environment which needs to be addressed by any organization to avoid negative incidence and low performance from its employees.